Factors Associated Defecting Carelessly Habits in Muara Sipongi District, Mandailing Natal Regency - Ita Fitriyani Lubis; Nurmaini Nurmaini; Taufik Ashar (RIRAI Publisher, 2023)
The achievement of proper hygiene and sanitation such as healthy latrine ownership is an aim of sustainable development from SDGs (Sustainable Development Goals). WHO data states that poor sanitation is one of the causes of death from diarrhea through water borne diseases to reach 3.4 million/years. This study aims to analyze the factors that affect defecating habits in Muara Sipongi Mandailing Natal District. The type of research is quantitative with cross sectional design. The population and samples are households that do not have as many as 200 households. The results showed that there was no relationship with income = 0.394 (P> 0.05), there was a relationship with knowledge, home distance and water availability of each value P = 0.001 (P <0.05) with the habit of defecation carelessly. It is advisable to the community to try to build latrines in every house or use facilities that have been provided from the local government such as public latrines so that there is no disease through feces. To each head of the family to encourage family members to defecate in their place and forbid neighbors to defecate carelessly near the house and in a stupid.